Maternal Depressive Symptoms and Adolescent Alcohol Use: The Mediating Role of Youth Depressive Symptoms. (April 2017) - Herman-Stahl, Mindy; Saavedra, Lissette M.; Morgan-Lopez, Antonio A.; Novak, Scott P.; Warner, Tara D.; Fishbein, Diana H.
The purpose of this study was to explore the influence of maternal depressive symptoms on adolescent alcohol use among a sample of Latino/Latina youth aged 10 to 16 years from a high-risk community. Direct and mediating effects of youth depressive symptoms, controlling for levels of concurrent emotion dysregulation, on alcohol use were examined. Participants consisted of 525 children and their mothers randomly sampled from low-income schools with high rates of substance use. The panel design included four waves, and we used structural equation modeling with a longitudinal mediational framework. Results indicated that the relationship between maternal depressive symptoms and adolescent alcohol use was mediated by adolescents' symptoms of depression for girls only. Findings are discussed in the context of the development of skills to cope with negative affect and the influence parental depressive symptoms may have on this process.